Electron-Proton Resonance Propagates a Delocalized Proton Wavepacket─A Vibronic Understanding of Picosecond Oscillatory Spectra in Proton Transfer - Zhang, Luhao; Fassioli, Francesca; Li, Rong; Scholes, Gregory D. (Journal of Physical Chemistry A, 2025)
Ultrafast spectroscopy of excited-state intramolecular proton transfer (ESIPT) has revealed picosecond oscillatory dynamics that are usually attributed solely to vibrational coherence. This study explores the possibility that, instead, vibronic coherence among reactant and product electron-proton vibronic states underlies the oscillatory signal. We develop and apply a model for ESIPT to two different chromophores (HBT and HBQ), which is based on a vibronic Hamiltonian comprising four electronic states coupled to proton and skeleton coordinates, with dynamics simulated through a master equation of Lindblad form that accounts for quantum coherent evolution and dissipation on an equal footing. We find that, under conditions of resonance between the proton vibrational frequency and the reactant-product electronic energy gap, the reaction involves vibronic states delocalized on the reactant and product. The ensuing reactant and product electronic population dynamics, exhibiting quantum coherent oscillations, are shown to translate into the “fast rise + oscillatory” time-resolved fluorescence (TRF) signals. In our model, the low-frequency skeletal vibration acts as a perturbation of the coupled electron-proton dynamics.
CRIS-Team Scopus Importer:2025-06-06